(untitled) (Agricultural Engineering, 2017)
The continuous technological development requires the use of modern materials also in agricultural engineering. Knowledge of the characteristics of tribological materials pairs cooperating with each other is useful for developing sliding nodes of agricultural machinery. Tribological properties of materials should be assessed for selection of technological materials beyond the economic criterion. The article presents analysis of the characteristics of tribological ball-on-disc wear of polymeric materials used as sliding elements for farm machines. Tribological tests were carried out under dry friction for a polymer-metal pair, and a wear rate and friction coefficient of the sample; the signs of wear were submitted to SEM observations.